Prevalence of human papillomavirus in high-grade intraepithelial lesions in women consulting in Latin American health systems. 2010-2019 - Mejía Sorto, Estefany Marleny; Henríquez Iraheta, Florenz Johana (La Universidad, 2022)
The article presents an analysis of prevalence of human papillomavirus in highgrade intraepithelial lesions in women who consult in the health systems in Latin America and Caribbean from 2010 to 2019; methodologically, through a documentary prevalence study, data are obtained that allows to observe the current situation of the human papillomavirus (HPV) and its relationship with cervical cancer, identifying the HPV serotype and the most frequent risk factors for Latin America and the Caribbean; in order to sensitize the population in general about the problem which in recent years has been trending upwards.